2021
DOI: 10.1159/000515395
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Periods for Adult Traumatic Brain Injuries: A Nationwide Population-Based Study

Abstract: <b><i>Introduction:</i></b> There is minimal existing available information on nationwide seasonal peaks in traumatic brain injuries (TBIs). This lack of information is an impediment to the effective development of prevention programs, societal policies, and hinders the resourcing of medical emergency services. Our current aim is to study nationwide population-based high-risk periods TBI over a 15-year study period in Finland. <b><i>Methods:</i></b> Nationwide da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, it is known that in Finland, as in many other countries, the incidence rate of TBIs among older people is currently increasing 10,20–22 . On the contrary, we have recently reported that at the same time, TBIs in leisure time are becoming more common among young and healthy individuals 23 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, it is known that in Finland, as in many other countries, the incidence rate of TBIs among older people is currently increasing 10,20–22 . On the contrary, we have recently reported that at the same time, TBIs in leisure time are becoming more common among young and healthy individuals 23 …”
Section: Discussionmentioning
confidence: 84%
“…10,[20][21][22] On the contrary, we have recently reported that at the same time, TBIs in leisure time are becoming more common among young and healthy individuals. 23 Significant variation in the incidence rates of TBI-related admissions in Europe has been reported depending on the country, region, study period, and age group. Reported incidence rates in regional populations or hospital catchment areas have previously been reported to be somewhat higher than in nationwide studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate and severe TBI as well as general trauma admissions peak during the weekends ( Bjarkø et al., 2019 ; Cantwell et al., 2015 ). Contrary to the observed trend in TBI with most patients being older and having associated comorbidities, weekend admissions are predominated by younger, healthier patients often admitted with coexisting alcohol intoxication ( Bjarkø et al., 2019 ; Posti et al., 2021 ). The hypothesis that weekend admissions are associated with increased mortality rate is termed “weekend effect” and it has been demonstrated in various medical conditions for instance myocardial infarction and stroke ( Kostis et al., 2007 ; Mekonnen et al., 2020 ).…”
Section: Introductionmentioning
confidence: 81%
“…However, differential mortality was not seen in a study of a Level 1 trauma center comparing the days of the week, possibly due to trauma teams being adequately staffed throughout the week ( Carr et al., 2010 ). There are few studies on TBI-related mortality during the weekend, but a recent Finnish study recognized increased mortality rate ( Posti et al., 2021 ) while another study solely focusing on older patients (>65 years) with moderate and severe TBI reported increased mortality rate during the weekends ( Schneider et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on date provided by the World Health Organization, traumatic brain injury (TBI) is the third leading cause of death globally 1 , accounting for nearly half of all injury-related deaths worldwide 1 , 2 . Moreover, TBI is a major cause of acquired disability worldwide; however, effective treatment methods are scarce 3 .…”
Section: Introductionmentioning
confidence: 99%